2003
DOI: 10.1002/ejoc.200300327
|View full text |Cite
|
Sign up to set email alerts
|

New 4′‐Functionalized 2,2′:6′,2′′‐Terpyridines for Applications in Macromolecular Chemistry and Nanoscience

Abstract: The well‐known reaction of 4′‐chloro‐2,2′:6′,2′′‐terpyridine with alkoxide nucleophiles leads to 4′‐functionalized 2,2′:6′,2′′‐terpyridines. This reaction allows the easy introduction of different functional groups onto the terpyridine at the 4′‐position, i.e. opposite to the metal binding site, in one reaction step. Among the functionalized 2,2′:6′,2′′‐terpyridines reported here are amines (including chiral examples), carboxylic acids, simple alkoxy‐chain terpyridines with different chain lengths, and a stilb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 37 publications
(22 reference statements)
1
40
0
Order By: Relevance
“…Both the Schubert and Constable groups could show that alkoxy-functionalized terpyridines 15 and 16 ( Figure 15 a) can be assembled into highly ordered architectures on graphite surfaces. [58][59][60] The STM was utilized to study the adsorbed terpyridines at the solid/liquid interface of highly ordered pyrolytic graphite (HOPG); well-ordered 2D arrays of 15 were observed on HOPG in 1-phenyloctane (Figure 15 b). Large ( > 500 nm), well-defi ned lamellar domains could be visualized.…”
Section: Progress Reportmentioning
confidence: 99%
“…Both the Schubert and Constable groups could show that alkoxy-functionalized terpyridines 15 and 16 ( Figure 15 a) can be assembled into highly ordered architectures on graphite surfaces. [58][59][60] The STM was utilized to study the adsorbed terpyridines at the solid/liquid interface of highly ordered pyrolytic graphite (HOPG); well-ordered 2D arrays of 15 were observed on HOPG in 1-phenyloctane (Figure 15 b). Large ( > 500 nm), well-defi ned lamellar domains could be visualized.…”
Section: Progress Reportmentioning
confidence: 99%
“…[21][22][23] A recent review also appeared on STM spectroscopy of magnetic molecules. [24] Several studies have been reported on ruthenium compounds measured by STM [25][26][27][28][29][30][31][32][33][34][35][36] and also on ruthenium and tris(diketonato) ligands, [37][38][39][40][41][42] but very few on adsorption of ruthenium or metal acetylacetonate (acac) complexes and their derivatives. [43,44] It is then of interest to synthesize and characterise Ru complexes including ligands that are favoured for their evaporation and adsorption for further investigations using STM and related techniques such as scanning tunnelling spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, terpy and its multiple derivatives have been used advantageously as building blocks for the engineering of novel supramolecular structures such as spiral lines, [26] dendrimers, [27] micelles, [28] polymers, [29,30] and liquid-crystalline soft materials. [31] Formation of ordered architectures on surfaces, [32][33][34] functional molecular devices, [35] and biochemical applications [36] are particularly challenging.…”
Section: Introductionmentioning
confidence: 99%